2020
DOI: 10.18295/squmj.2020.20.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Caffey Disease in Infancy: A diagnostic dilemma for primary care physicians

Abstract: Caffey disease is a rare and self-limiting condition characterised by cortical hyperostosis with inflammation of adjacent fascia and muscles. It usually presents in infancy and clinical features include hyperirritability, acute inflammation with swelling of overlying soft tissues and subperiosteal new bone formation. Awareness of the existence of this rare condition and its typical clinical and radiological profile will avoid unnecessary investigations and treatment and help the physician to explain its good p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…It presents with swelling of surrounding soft tissues and may be accompanied by fever and irritability. The disease manifests in infancy typically, the first 6 months of life 4. It is frequently sporadic; however, there have been isolated cases of autosomal dominant or recessive forms 5.…”
Section: Discussionmentioning
confidence: 99%
“…It presents with swelling of surrounding soft tissues and may be accompanied by fever and irritability. The disease manifests in infancy typically, the first 6 months of life 4. It is frequently sporadic; however, there have been isolated cases of autosomal dominant or recessive forms 5.…”
Section: Discussionmentioning
confidence: 99%
“…3 It is a rare, self-limiting disorder which is characterised by an acute inflammation of the periosteum and the covering soft tissues. 1,4 The characteristic triad of Caffey disease consists of systemic symptoms (irritability and fever), soft tissue swelling and underlying cortical bone thickening. 2 The exact aetiology of this disorder is still unclear however it has been reported that the autosomal dominant form of Caffey disease is caused by recurrent argininecysteine (R836C) substitution in the α1 chain of type I collagen.…”
Section: Discussionmentioning
confidence: 99%
“…4 Caffey disease is a disorder of early infancy with its onset within first six months of life which usually resolves by two years of age. 1 The most frequently involved site is mandible (70-90%) followed by clavicle, ribs, scapula and long bones. 4 Laboratory f i n d i n g s i n c l u d e e l e v a t e d E r y t h r o c y t e Sedimentation Rate (ESR), high level of C-R e a c t i v e p r o t e i n s ( C R P ) , h i g h a l k a l i n e phosphatase, thrombocytosis, anaemia and raised immunoglobulin levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations